Fixation probabilities in evolutionary games with the Moran and Fermi processes. (7th January 2015) - Liu, Xuesong; Pan, Qiuhui; Kang, Yibin; He, Mingfeng
Abstract: An evolutionary dynamic model of 2×2 games with finite population of size N + M was built. Among these individuals, N individuals have the same update mechanism as that of the Moran process, while the other M individuals have the same update mechanism as that of the Fermi process. We obtain the balance equations of the fixation probability and analyze some concrete cases. In contrast with the results of neutral evolution, the fixation probability of a single co-operator with the same update mechanism as that of the Fermi process is higher. Besides, more co-operators with the update mechanism of the Fermi process lead to higher fixation probabilities when co-operators׳ quantity is the same. Highlights: A Moran and Fermi mixed process is proposed. Fixation probability of a single co-operator with update mechanism of the Fermi process is higher than neutral evolution׳s. More co-operators with update mechanism of the Fermi process lead to higher fixation probabilities when co-operators׳ quantity is the same.